Autonomy–Connectedness, Self-Construal, and Acculturation: Associations With Mental Health in a Multicultural Society. (January 2019) - Maas, J.; van Assen, M. A. L. M.; van Balkom, A. J. L. M.; Rutten, E. A. P.; Bekker, M. H. J.
The present study investigated the associations between self-construal, acculturation, and autonomy–connectedness, as well as the relations between autonomy–connectedness and psychopathological symptoms, controlling for self-construal and acculturation. Participants were 1, 209 Dutch individuals, of whom 693 (57.3%) were immigrants with a non-Western background. Results showed that an independent self-construal was positively associated with self-awareness and capacity for managing new situations, and was negatively associated with sensitivity to others (which are the three components of autonomy–connectedness). Moreover, an interdependent self-construal was negatively associated with self-awareness and capacity for managing new situations, and was positively associated with sensitivity to others. Importantly, the latter associations were similar for both Dutch natives and immigrants, and the associations between acculturation and autonomy–connectedness were small and nonsignificant. Autonomy–connectedness, after controlling for self-construal and acculturation, explained a large amount of additional variance in anxiety (12.7%) and depression (14.1), and a medium amount of additional variance in drive for thinness (3.7%) and bulimia (4.8%). Autonomy–connectedness, thus, seems to be an important construct for people with a Western background, as well as for immigrants with a non-Western background.